0
$\begingroup$

If $x,y>0$ satisfying the system of equations $x^{x+y}=y^n$ and $y^{x+y}=x^{2n}y^n$, where $n>0$ then prove that $y=\dfrac{1+4n-\sqrt{1+8n}}{2}$

$$ (xy)^{x+y}=(xy)^{2n}\implies x+y=2n\\ x^{2n}=y^n\implies x^2=y\\ x^{2}=2n-x\implies x^2+x-2n=0\\ x=\frac{-1\pm\sqrt{1+8n}}{2}\implies x=\frac{-1+\sqrt{1+8n}}{2}\\ y=x^2=\frac{2+8n-2\sqrt{1+8n}}{4}=\frac{1+4n-\sqrt{1+8n}}{2} $$ Fine, but if I do the opposite $$ y=x^2=(2n-y)^2=4n^2+y^2-4ny\\ y^2-(4n+1)y+4n^2=0\\ y=\frac{1+4n\pm\sqrt{1+8n}}{2} $$ In the second approach how do I eliminate the other case ?

Attempt $$ y=x^2=\frac{1+4n\pm\sqrt{1+8n}}{2}=\frac{2+8n\pm2\sqrt{1+8n}}{4}=\bigg[\frac{1\pm\sqrt{1+8n}}{2}\bigg]^2\\ \implies x=\bigg|\frac{1\pm\sqrt{1+8n}}{2}\bigg| $$ $$ y=\frac{1+4n+\sqrt{1+8n}}{2}\implies x=\frac{1+\sqrt{1+8n}}{2} $$ $$ y=\frac{1+4n-\sqrt{1+8n}}{2}\implies x=\frac{-1+\sqrt{1+8n}}{2} $$ Still getting two cases ?

$\endgroup$
1
$\begingroup$

Note that $x+y=2n$, and since $x,y,n$ are positive, it must be that $x=2n-y>0$, that is, $y<2n$. However, the superfluous solution does not satisfy this.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.